Recovery kinetics after speed-endurance training in male soccer players - Tzatzakis, T.; Papanikolaou, K.; Draganidis, D.; Tsimeas, P.; Kritikos, S.; Poulios, A.; Laschou, V. C.; Deli, C. K.; Chatzinikolaou, A.; Batrakoulis, A.; Basdekis, G.; Mohr, M.; et al. (International Journal of Sports Physiology and Performance, 2020)
Purpose: To determine the recovery kinetics of performance, muscle damage, and neuromuscular fatigue following 2 speed-endurance production training (SEPT) protocols in soccer. Methods: Ten well-trained, male soccer athletes randomly completed 3 trials: work-to-rest ratio (SEPT) 1:5, SEPT/1:8, and a control trial. Training load during SEPT was monitored using global positioning system and heart-rate monitors. Performance (isokinetic strength of knee extensors and flexors, speed, and countermovement jump) and muscle damage (delayed-onset muscle soreness [DOMS] and creatine kinase) were evaluated at baseline and at 0, 24, 48 and 72 h posttraining. Maximal voluntary contraction (fatigue index) of knee extensors and flexors was additionally assessed at 1, 2, and 3 h posttraining. Results: Fatigue increased (P<.05) in SEPT/1:5 (~4-30%) for 3 h and in SEPT/1:8 (~8-17%) for 2 h. Strength performance declined (P<.05) in both SEPT trials (~5-20%) for 48 h. Speed decreased (~4-18%; P<.05) for 72 h in SEPT/1:5 and for 48 h in SEPT/1:8. Countermovement-jump performance decreased (~7-12%; P<.05) in both SEPT trials for 24 h. DOMS increased (P<.05) in SEPT/1:5 (~2-fold) for 72 and in SEPT/1:8 (~1- to 2-fold) for 48 h. Creatine kinase increased (~1- to 2-fold, P<.05) in both SEPT trials for 72 h. Conclusions: SEPT induces short-term neuromuscular fatigue; provokes a prolonged deterioration of strength (48 h), speed (72 h), and jump performance (24 h); and is associated with a prolonged (72-h) rise of DOMS and creatine kinase. Time for recovery is reduced when longer work-to-rest ratios are applied. Fitness status may affect quality of SEPT and recovery kinetics.